2011
DOI: 10.1177/0194599811400369
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Pain in Pediatric Patients Undergoing Coblation Tonsillectomy versus Cautery Tonsillectomy

Abstract: Pediatric pain is similar following monopolar electrocautery or coblation subcapsular tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Given the findings of our study and other studies that have shown no significant difference in pain between these techniques, we ask the question of whether the cost of coblation can be justified . As health care costs shift from insurance companies to hospitals and physicians, physicians must become more accountable for the costs of their decisions, including equipment .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Given the findings of our study and other studies that have shown no significant difference in pain between these techniques, we ask the question of whether the cost of coblation can be justified . As health care costs shift from insurance companies to hospitals and physicians, physicians must become more accountable for the costs of their decisions, including equipment .…”
Section: Discussionmentioning
confidence: 84%
“…Post‐operative pain can continue for up to 2 weeks and can lead to decreased oral intake and dehydration requiring hospital readmission . Despite many prospective studies comparing these methods to determine which one causes less post‐operative pain, there is not a clear consensus …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, bipolar radiofrequency ablation (coblation) significantly limits thermal heat to 40°C to 70°C through the use of irrigating saline and its bipolar component, providing a theoretical decrease in collateral tissue damage. Although several studies suggest a decreased need for postoperative analgesia with intracapsular coblation techniques, a recent Cochrane review concluded the evidence supporting decreased postoperative pain with radiofrequency ablation to be inadequate . Other reports examining radiofrequency ablation have cited an increase in postoperative hemorrhage and surgical costs .…”
Section: Introductionmentioning
confidence: 99%